1995
DOI: 10.1002/ana.410380109
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor function in amyotrophic lateral sclerosis: Evidence for frontal impairment

Abstract: Saccadic eye movements, fixation, and smooth pursuit were recorded in 17 subjects with amyotrophic lateral sclerosis (ALS) and 11 age-matched controls using a magnetic scleral search coil. Reflexive, remembered and antisaccades, and smooth pursuit at four target velocities were studied. Subjects with ALS showed significantly elevated error rates (distractibility) and latency in the antisaccade and remembered saccade paradigms but no abnormality of reflexive saccades. The frequency of small saccades that intrud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
2
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 29 publications
11
83
2
5
Order By: Relevance
“…In particular, they were found to be larger in spinal-onset patients compared to controls (p = 0.04). Although a previous study [37] found an increase in the number of saccadic intrusions during fixation in patients with MND, only square wave jerks were included. Square wave jerks are only a component of all the small involuntary saccades that intrude on fixation [1] and therefore their study cannot be a true reflection of fixation in MND.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, they were found to be larger in spinal-onset patients compared to controls (p = 0.04). Although a previous study [37] found an increase in the number of saccadic intrusions during fixation in patients with MND, only square wave jerks were included. Square wave jerks are only a component of all the small involuntary saccades that intrude on fixation [1] and therefore their study cannot be a true reflection of fixation in MND.…”
Section: Discussionmentioning
confidence: 99%
“…Although eye movements are classically spared in MND some patients have been reported with a range of ocular motor disorders including nystagmus, saccadic hypometria [28], slowed saccades [8,33], increased saccadic latencies [25], decreased smooth pursuit gain [3,23,25, 32] and saccadic interruptions of smooth pursuit [20] although these studies were small and often predated the El Escorial criteria. The most comprehensive study to date [37], however, found increased antisaccadic error rates and latencies with relative preservation of reflexive saccades suggesting frontal lobe dysfunction. A disturbance of fixation was also noted and patients were found to have ■ Abstract Objective Eye movements are classically felt to be spared in motor neurone disease (MND).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Subjects with large frontal lobe lesions are known to display high distractibility in the antisaccade task [25], and recent lesion studies and functional imaging studies in man suggest that this effect in both the antisaccade and remembered saccade paradigms relates more specifically to dysfunction of dorsolateral prefrontal cortex (DLPFC) [26][27][28]. High levels of distractibility are also reported in other patient groups in whom frontal lobe function is impaired, including schizophrenia [29], Huntington's disease [30], motor neuron disease [31], and progressive supranuclear palsy [32].…”
Section: Discussionmentioning
confidence: 95%
“…Em outros pacientes, a eletro-oculografia (34) consegue revelar dificuldades nos movimentos voluntários sacá-dicos, nos de convergência e perseguição ou alterações do reflexo vestíbulo-ocular, do nistagmo optocinético (38) ou do fenômeno de Bell (39) , indicando lesão nas vias córtico-óculo-motoras e sugerindo distúrbio supranuclear extrapiramidal (40) , ou supratentorial piramidal (41) . O aumento na taxa de erros nos testes neuropsicológicos óculo-motores também tem sido associado a uma disfunção do córtex frontal (42)(43) . A melhora dos movimentos sacádicos verticais (mas não do resto do corpo) com uso de hormônio libertador da tirotrofina (44) poderia estar refletindo um mecanismo fisiopatológico diferente com perda celular no núcleo intersticial do fascículo longitudinal medial e na substância nigra (45) .…”
Section: Discussionunclassified